Financial Technology: An Overview on Shariah and Legal Implication - Izzat Amsyar Mohd Arif, Mohd; Hakimah binti Ab Halim, Asma; `Afifi bin Ab Halim, Mustafa (KnE Social Sciences, 2024)
Technological progress affects many things and practices in today’s life. In addition to the occurrence of the COVID-19 pandemic, it leads to a more open and almost comprehensive use of technology. This effect also occurs in the financial aspect. The emergence of various forms of technology-based transactions also has implications for legislation and sharia. This study was conducted qualitatively through the analysis of literature and legal sources from selected countries such as Malaysia and Indonesia. The study found that there is a law that has been drafted to regulate this aspect as well as a fatwa issued to lay the foundation for this transaction from a contractual point of view according to the Syariah perspective. However, further research still needs to be done considering that various forms of innovation involve transactions that have taken place and each of them requires clarification from a legal point of view as well as jurisprudence adaptation. Keywords: financial technology, Shariah, legal, implication